Embedding supportive parenting resources into maternity and early years care pathways: a mixed methods evaluation - Nicola Crossland; Gill Thomson; Victoria Hall Moran (BMC, 2019)
Abstract Background During pregnancy and postnatally, women seek information from a variety of sources. The potential to incorporate educational pregnancy and parenting resources into conventional health services is underexplored. In 2014-2016, UK-based charity Best Beginnings used an embedding model to embed three of their resources - the Baby Buddy app, Baby Express magazine, and 'From Bump to Breastfeeding' DVD - into maternity and early years care pathways at three sites in the north of England. A mixed-methods evaluation comprising an impact evaluation and a process evaluation was undertaken. Here we report findings from the process evaluation that aimed to understand the embedding process, explore maternity and early years' professionals' views and use of the resources, explore women's engagement with and views of the resources, and identify barriers and facilitators to the embedding process. Methods We carried out semi-structured interviews with stakeholders (professionals involved in embedding) and observations of embedding activities to understand how embedding worked. Surveys of postnatal women were conducted over a two-month period both prior to, and after, the resources had been embedded, to ascertain engagement with and views of the resources. A survey of professionals was carried out post-embedding to understand how, where and when the resources were used in practice, and professionals' views. Descriptive and thematic analyses were undertaken. Results Thirty stakeholders took part in interviews. Surveys were completed by 146 professionals, and by 161 and 192 women in the pre and post-embedding phases respectively. Themes derived from analysis of qualitative data were 'Implementation of the embedding model', 'Promotion and distribution of, and engagement with, the resources', 'Fit with care pathways', and 'Perceptions of the resources'. While survey responses indicated that embedding of the resources into practice was not yet complete, those who had used the resources believed that they had helped increase knowledge, build confidence and support relationship-building. Conclusions Incorporating supportive parenting resources into maternity and early years' care pathways requires a planned embedding approach, committed champions, and senior management support. Findings indicate largely positive views of women and professionals, and suggest the resources can be a beneficial aid for families.